Integrated proteogenomic approach identifying a protein signature of COPD and a new splice variant of SORBS1. Issue 2 (14th January 2020) - Brandsma, Corry-Anke; Guryev, Victor; Timens, Wim; Ciconelle, Ana; Postma, Dirkje S; Bischoff, Rainer; Johansson, Maria; Ovchinnikova, Ekaterina S; Malm, Johan; Marko-Varga, Gyorgy; Fehniger, Thomas E; van den Berge, Maarten; et al.
Abstract : Translation of genomic alterations to protein changes in chronic obstructive pulmonary disease (COPD) is largely unexplored. Using integrated proteomic and RNA sequencing analysis of COPD and control lung tissues, we identified a protein signature in COPD characterised by extracellular matrix changes and a potential regulatory role for SUMO2. Furthermore, we identified 61 differentially expressed novel, non-reference, peptides in COPD compared with control lungs. This included two peptides encoding for a new splice variant of SORBS1, of which the transcript usage was higher in COPD compared with control lungs. These explorative findings and integrative proteogenomic approach open new avenues to further unravel the pathology of COPD.